Vascular aging, the vascular cytoskeleton and aortic stiffness - Lova Prasadareddy Kajuluri; Kuldeep Singh; Kathleen G Morgan (Open Exploration Publishing Inc., 2021)
Vascular aging, aortic stiffness and hypertension are mechanistically interrelated. The perspective presented here will focus mainly on the molecular mechanisms of age-associated increases in the stiffness of the vascular smooth muscle cell (VSMC). This review will highlight the mechanisms by which the VSMC contributes to disorders of vascular aging. Distinct functional sub-components of the vascular cell and the molecular mechanisms of the protein-protein interactions, signaling mechanisms and intracellular trafficking processes in the setting of the aging aorta will be detailed.